Granulatosides D, E and other polar steroid compounds from the starfish Choriaster granulatus. Their immunomodulatory activity and cytotoxicity. Issue 18 (17th September 2019) - Ivanchina, Natalia V.; Kicha, Alla A.; Malyarenko, Timofey V.; Ermolaeva, Sofiya D.; Yurchenko, Ekaterina A.; Pislyagin, Evgeny A.; Van Minh, Chau; Dmitrenok, Pavel S.
Abstract: Two new steroid glycosides, granulatosides D (1 ) and E (2 ), belonging to the group of bi- and monoglycosides of polyhydroxysteroids, respectively, were isolated from the ethanolic extract of the starfish Choriaster granulatus along with thirteen previously known glycosides of polyhydroxysteroids (3 –15 ) and one steroid heptaol (16 ). The structures of the new compounds were elucidated by extensive NMR and ESIMS techniques. Cytotoxic and immunomodulatory activities of compounds1, 3 –8, and10 –16 using murine splenocytes and peritoneal macrophages were studied. At a dose of 0.1 μM new glycoside1 showed immunomodulatory properties, increasing the intracellular ROS (reactive oxygen species) level in peritoneal murine macrophages by 20% and decreasing intracellular ROS level by 21% in pre-treated with endotoxic lipopolysaccharide from E. coli (LPS) peritoneal macrophages. Abstract :